Supplementation with antioxidants and folinic acid for children with Down's syndrome: randomised controlled trial. Issue 7644 (21st February 2008) - Ellis, Jill M; Tan, Hooi Kuan; Gilbert, Ruth E; Muller, David P R; Henley, William; Moy, Robert; Pumphrey, Rachel; Ani, Cornelius; Davies, Sarah; Edwards, Vanessa; Green, Heather; Salt, Alison; et al.
Abstract : Objectives To assess whether supplementation with antioxidants, folinic acid, or both improves the psychomotor and language development of children with Down's syndrome. Design Randomised controlled trial with two by two factorial design. Setting Children living in the Midlands, Greater London, and the south west of England. Participants 156 infants aged under 7 months with trisomy 21. Intervention Daily oral supplementation with antioxidants (selenium 10 μg, zinc 5 mg, vitamin A 0.9 mg, vitamin E 100 mg, and vitamin C 50 mg), folinic acid (0.1 mg), antioxidants and folinic acid combined, or placebo. Main outcome measures Griffiths developmental quotient and an adapted MacArthur communicative development inventory 18 months after starting supplementation; biochemical markers in blood and urine at age 12 months. Results Children randomised to antioxidant supplements attained similar developmental outcomes to those without antioxidants (mean Griffiths developmental quotient 57.3 v 56.1; adjusted mean difference 1.2 points, 95% confidence interval −2.2 to 4.6). Comparison of children randomised to folinic acid supplements or no folinic acid also showed no significant differences in Griffiths developmental quotient (mean 57.6 v 55.9; adjusted mean difference 1.7, −1.7 to 5.1). No between group differences were seen in the mean numbers of words said or signed: for antioxidants versus none the ratio of means was 0.85 (95% confidence interval 0.6 to 1.2), and for folinic acid versus none it was 1.24 (0.87 to 1.77). No significant differences were found between any of the groups in the biochemical outcomes measured. Adjustment for potential confounders did not appreciably change the results. Conclusions This study provides no evidence to support the use of antioxidant or folinic acid supplements in children with Down's syndrome. Trial registration Clinical trials NCT00378456 .